MADRASAH MODERNIZATION: THE KEY ROLE OF COMMUNICATION IN BUILDING A POSITIVE IMAGE - Juwita, Juwita; Rifa’i, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research focuses on the modernization of madrasas through optimizing communication to build a positive image of educational institutions. This study was carried out at MA Miftahul Ulum Besuki, using a qualitative approach with a case study research type. Data were collected through observation, interviews with the head of the madrasah, teachers, and students, and documentation. Data analysis follows the stages of data reduction, data presentation, and verification, using content analysis and interpretation methods to explore the relationship between communication practices and institutional image.The research results show that strategic communication implemented through digital media and direct interaction can increase transparency, share student and alums success stories, and convey superior madrasa programs effectively. This has a positive impact on public perception of madrasas. However, challenges were also found in the consistent delivery of information and use of technology by all stakeholders.The implication of this research is the importance of integrated communication planning as part of the madrasah modernization strategy to ensure that the community can receive the educational values and innovations that are well.